Case Report: Differential Genomics and Evolution of a Meningeal Melanoma Treated With Ipilimumab and Nivolumab - Burgos, Remberto; Cardona, Andrés F.; Santoyo, Nicolas; Ruiz-Patiño, Alejandro; Cure-Casilimas, Juanita; Rojas, Leonardo; Ricaurte, Luisa; Muñoz, Álvaro; Garcia-Robledo, Juan Esteban; Ordoñez, Camila; Sotelo, Carolina; Rodríguez, July; et al. (Frontiers in Oncology, 2022)
Primary melanocytic tumors of the CNS are extremely rare conditions, encompassing different disease processes, including meningeal melanoma and meningeal melanocytosis. Its incidence range between 3-5%, with approximately 0.005 cases per 100,000 people. Tumor biological behavior is commonly aggressive, with poor prognosis and very low survivability, and a high recurrence rate, even after disease remission with multimodal treatments. Specific genetic alterations involving gene transcription, alternative splicing, RNA translation, and cell proliferation are usually seen, affecting genes like BRAF, TERT, GNAQ, SF3B1, and EIF1AX. Here we present an interesting case of a 59-year-old male presenting with neurologic symptoms and a further confirmed diagnosis of primary meningeal melanoma. Multiple therapy lines were used, including radiosurgery, immunotherapy, and chemotherapy. The patient presented with two disease relapses and an evolving genetic makeup that confirmed the disease's clonal origin. We also provide a review of the literature on the genetic basis of primary melanocytic tumors of the CNS.